Functional Load and the Teaching-Learning Relationship in L2 Pronunciation - Sewell, Andrew (Frontiers in Communication, 2021)
Though frequent recourse has been made to the functional load (or FL) principle in establishing priorities for L2 pronunciation teaching, it remains an under-theorized and relatively under-utilized concept. This is despite the existence of empirical evidence pointing to correlations between the FL ranking of phonemic contrasts and a) the effect that the absence of particular contrasts has on the comprehensibility of speech, and b) their occurrence at different levels of proficiency. Munro and Derwing (2006) found that sentences with divergences in high FL contrasts (e.g., when /z/ was substituted by/d/) were rated as significantly less comprehensible than sentences containing divergences in low FL contrasts (e.g., when /d/ was substituted by/ð/). Kang and Moran (2014) found that as the proficiency level of test-takers increased, the number of errors involving high FL contrasts dropped significantly. Taken together, these findings suggest that language learners tend to pay more attention to high FL contrasts and incorporate them into their repertoires more readily than low FL contrasts. The concept of FL therefore appears to be relevant in considering the relative ease (or difficulty) of learning and teaching particular features, and in understanding the relationship between learning and teaching. Frequent calls have been made for FL considerations to inform the setting of priorities in L2 pronunciation teaching, for example. In this mini-review I will explore and re-evaluate the concept of FL in terms of both theoretical formulation and empirical application, aiming to identify both its contributions and its limitations.